2008
DOI: 10.1111/j.1872-034x.2008.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance between lipid metabolism‐associated genes and rat liver regeneration

Abstract: According to the results of the chip detection, it was presumed that fatty acid synthesis at 24-66 h, leukotriene and androgen synthesis at 16-168 h, prostaglandin synthesis at 2-96 h, triglyceride synthesis at 18-24 h, glycosphingolipid synthesis at 0.5-66 h, metabolism of phosphatidyl inositol and sphingomyelin at 2-16 h, and cholesterol catabolism at 30-168 h were enhanced. Throughout almost the whole LR, the genes participating in estrogen, glucocorticoid, and progesterone synthesis, and triglyceride catab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…S4 A). In agreement with previous studies [39][40][41], which suggested that the pre-existing cholesterol storage or the delivered lipoprotein cholesterol may be insufficient to meet the cellular required demand soon after the start of cell division in the regenerating liver (2-3 days after PH) while higher expression of HMGCR and its activity and strong new cholesterol synthesis are required. Interestingly, in the present study, we found that precursors of SREBP-2 were increased after PH (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…S4 A). In agreement with previous studies [39][40][41], which suggested that the pre-existing cholesterol storage or the delivered lipoprotein cholesterol may be insufficient to meet the cellular required demand soon after the start of cell division in the regenerating liver (2-3 days after PH) while higher expression of HMGCR and its activity and strong new cholesterol synthesis are required. Interestingly, in the present study, we found that precursors of SREBP-2 were increased after PH (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Liver regeneration (LR) represents a good model of synchronized proliferation in vivo that is very useful for studying events correlated with various phases of the cell cycle. The hepatocytes have low mitotic activity in adult rats and acquire the ability to divide during LR following partial hepatectomy (PH) re-entering rapidly in the cell cycle from the G0-phase [2,3]. G0/G1 phase transition occurs 4–6 h after PH, whereas cell proliferation 6–66 h after PH, characterized by G1/S phase transition at 6–12 h, DNA synthesis (S phase) at 18 h, S/G2 phase transition at 18–24 h and first cell division at 24 h after PH [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The hepatocytes have low mitotic activity in adult rats and acquire the ability to divide during LR following partial hepatectomy (PH) re-entering rapidly in the cell cycle from the G0-phase [2,3]. G0/G1 phase transition occurs 4–6 h after PH, whereas cell proliferation 6–66 h after PH, characterized by G1/S phase transition at 6–12 h, DNA synthesis (S phase) at 18 h, S/G2 phase transition at 18–24 h and first cell division at 24 h after PH [2,3]. For cell differentiation and liver tissue structure, functional rebuilding occurs 72–168 h after PH [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have looked at expression of: lipid metabolism-associated genes 88 ; genes associated with cellular immune response 89 and blood coagulation 90 ; cell junction-associated genes 91 ; and genes associated with the metabolism and transport of amino acids. 92 Each study identified a large number of genes which are up-or down-regulated during liver regeneration but unfortunately the studies did not determine whether the genes altered protein expression nor did they assess for polymorphisms of the genes concerned.…”
Section: Future Developmentsmentioning
confidence: 99%